Pengaruh Leverage, Pertumbuhan Penjualan, dan Perputaran PersediaanTerhadap Profitabilitas Pada Perusahaan Perdagangan SubsektorRitel yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2024 - Andrianus Alvin Fernando; Aminah Aminah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of leverage, sales growth, and inventory turnover on profitability in retail trading companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Profitability is an important indicator in assessing a company's financial performance because it reflects the company's ability to generate profits from its operational activities. The level of profitability of retail companies is influenced by various factors, including funding structure, the ability to increase sales, and the effectiveness of inventory management. This study uses a quantitative approach with an associative research type. The population in this study is all retail trading companies listed on the IDX, with a research sample of 10 companies selected using a purposive sampling technique based on certain criteria. The data used are secondary data in the form of the company's annual financial statements for the 2020–2024 period. Data analysis techniques used include descriptive statistics, classical assumption tests, multiple linear regression analysis, model feasibility tests (F tests), partial tests (t tests), and coefficient of determination (R²) tests. The results of the study indicate that partially, leverage and sales growth have a positive and significant effect on profitability, while inventory turnover has a significant, but negative, effect on profitability. Simultaneously, leverage, sales growth, and inventory turnover significantly influence the profitability of trading companies in the retail subsector.